(untitled) - Weldon, Gregory (Hoboken, N.J., 2007)
This lively book is packed with first-person war stories from the front lines of trading. But don't let its entertaining style fool you, because Gold Trading Boot Camp is also packed with specific detail and hands-on trading advice. This technique-driven handbook tells you which trading environments are tailor-made for building speculative wealth in gold trading, while at the same time explaining how to maximize your profitability from buying and selling gold in virtually every type of market environment. It features: A step-by-step, detailed accounting of the regimen that a successful gold trader, and any successful capital markets investor, should follow each and every trading day; A complete overview of the gold market's structure—essential for making consistently profitable trading decisions in this "tightly held" market; Strategies for using technical analysis and quantitative systems to accurately define significant trend reversals, major pivot points, continuation and correction patterns, and trend acceleration sequences; An overview of the macro-fundamentals that pinpoint the most pertinent economic indicators and information sources available. The author has crafted an approach that slices through today's overwhelming amount of data-noise and empowers you to make faster and more informed investment decisions; Market-proven methods for identifying trends, trading on momentum, and profiting from the natural movements of the market; A valuable reference library of long-term charts that accurately reflect the historic performance of gold and precious metals markets relative to other asset classes.
Keywords: Commodity exchanges,Gold,Gold,Gold; Purchasing; United States